Medical Errors in the Private Sector Where To? (Global Journal of Medical Research, 2014)
To study the issues of medical errors in the private health sector and determine the conviction rate in the decisions by specialty on the defendants from health professions. The total number of decisions issued by the Health Authority within five years 331 resolution and the conviction rate (Number = 192, 58%) were distributed into the following health facilities: private hospitals (n = 248, 74.9%), private clinics (n = 56, 16.9%) and private dispensaries (n = 27, 8.2%). Total 252 out of 845 of defendants health professions were convicted, they are distributed as follows: Doctors (n = 236, 93.7%), nurses and midwives (n = 13, 5.2%), technicians (n = 2, 0.8%) and other professionals (n = 1, 0.4%). The conviction rate in five years is on the rise and thus this is reflected on the trend of medical errors into upward in the private health sector.
Keywords: condemnation; plaintiff right; decisions; judgments; health staff; mistakes; health facilities